Livelihood vulnerability household fishermen household due to climate change in Lampung Province, Indonesia. - Maya Riantini; Maesti Mardiharini; Saptana; Bedy Sudjarmoko; Eka Kasymir; Lestari Gita Nur'aini; Salsa Hentia Anindita; Mat Syukur; Armen Zulham; Budi Wardono; I Ketut Ardana; Chandra Indrawanto; et al. (PLoS ONE)
The livelihood of small-scale fishers is highly dependent on marine resources and coastal areas while the condition of marine waters is increasingly unpredictable due to seasonal uncertainty and extreme weather due to climate variability. This condition has a negative impact on fish catches and the income of small-scale fishermen. The study results were obtained through interviews with respondents using a structured questionnaire. Sampling was carried out using multistage random sampling based on the type and number of ships controlled (1 GT-5GT). The total sample of respondents interviewed was 166 fishing households, consisting of 36 respondents from Bandar Lampung City, 65 respondents from South Lampung Regency, and 65 respondents from Tanggamus Regency. Data was evaluated using three analysis methods, namely household income structure, indicators of income vulnerability, and adaptation mechanisms. Income structure and income vulnerability use a quantitative approach, while adaptation mechanisms use a qualitative approach. The results of this empirical study found that the source of income of traditional capture fisher households is from: fishing business (on the farm) averaged 82.22%, in Tanggamus Regency, the proportion reached 86.22%. The income vulnerability index of traditional capture fisher households (LVI-IPCC value) in Bandar Lampung City and South Lampung Regency is positive (0.39 and 0.36). The income vulnerability index of traditional fishermen in Tanggamus Regency is negative -0.29. Fishermen employ an adaptation mechanism that engaged the five fundamental facets of income capital, namely natural capital, human capital, physical capital, financial capital, and social capital.